Investigation on amitraz, coumaphos and thymol concentrations in honey produced by Slovenian beekeepers in 2020 - Helena BAŠA ČESNIK; Veronika KMECL (Acta Agriculturae Slovenica)
A survey on concentrations of veterinary drug residues amitraz, coumaphos and thymol in honey, produced in year 2020 by Slovenian beekeepers, was conducted. 100 samples were analysed: 22 from organic and 78 from conventional production, with two analytical methods. In method for determination of coumaphos and thymol samples were extracted with acetone, petroleumether and dichlorometane. In method for determination of amitraz and its degradation products, samples were hydrolisated with HCl and NaOH, extractied with n-hexane and derivatisated with heptafluorobutyric anhydride. Determination in both methods was performed with gas chromatograph coupled with mass spectrometer. Measured concentrations of amitraz, coumaphos and thymol were in the range of 0.01-0.12 mg kg-1, 0.02-0.06 mg kg-1 and 0.08-0.17 mg kg-1, respectively. In 61 % of samples analysed no residues of amitraz, thymol and coumaphos were found. Data obtained were compared with the data from literature. Chronic and acute exposure were calculated for consumers. Maximum chronic exposure for amitraz and thymol was 0.1 % and 0.05 % of acceptable daily intake, respectively. Maximum acute exposure for amitraz and thymol was 4 % and 0.8 % of acute reference dose, respectively